Socioeconomic Factors Influencing Increased Mental Health Challenges among Pregnant and Parenting Adolescent Mothers Schooling in Secondary Schools of Muhanga District, Rwanda - Umugwaneza, Marie Alice; Maurice, B. Silali (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Adolescent motherhood is global public health challenges affecting mental health outcomes, in Rwanda 5% of adolescent girls begun childbearing, with the highest of 12% in Muhanga District where Mental health challenges affect 48.9% of adolescent mothers attending secondary schools with limited evidence on the factors influencing these mental health outcomes. The study aimed determine Socioeconomic Factors Influencing Mental Health challenges and assess how knowledge attitude and Practices influence the mental health outcomes of adolescent Mothers schooling Secondary Schools of Muhanga District. Descriptive cross-sectional, mixed-methods approach conducted among 235 secondary school adolescent mothers aged 15–19, using purposive and snowball sampling. Quantitative data were analysed with SPSS descriptive, Chi-square test, logic regression, Qualitative data were analysed thematically into saturation. The study opined the Social economic and Knowledge Attitudes and Practices both influenced significantly student adolescent mothers’ mental health challenges, majority 44% opined financial difficulties as one of the key challenges influencing mental health disorders .Extreme poverty (AOR=3.42, 95% CI:1.60 - 7.33, p = 0.002); distance to school (AOR=24.65, 95% CI: 6.11 – 99.45, p < 0.001),Academic financial support from parents (AOR = 0.26, 95% CI: 0.13 - 0.51, p < 0.001),family wealth on child care(AOR=3.63, 95% CI: 1.62 - 8.10, p=0.002),Strict cultural beliefs and practices (AOR = 23.51, 95% CI [8.49-65.12], p < .001), Forced sexual relations (AOR = 5.77, 95% CI 2.35-14.35, p < .001), Benefiting the chance to see the baby (AOR = 2.33, 95% CI 1.01-5.35, p = .046) were significantly related to influence mental health outcomes. The study showed significant influence of socioeconomic factors on mental health outcome in adolescent mothers, it recommends public health interventions addressing socio-economic and practices distress and policy reforms to enhance mental health and secondary educational attainment of adolescent mothers.